UPAYA MENINGKATKAN MINAT BELAJAR MATEMATIKA MENGGUNAKAN MODEL PEMBELAJARAN (PAKEM) DI SMA NEGERI 2 SIABU - Benny Sofyan Samosir; Nursahara Nursahara; Ahmad Fadil Pohan (Jurnal Karya Pendidikan Matematika, 2020)
Increase students' interest in learning Mathematics by using Active, Creative, Effective and Enjoyable Learning (PAKEM) models on the subject of trigonometric ratios on right triangles. Subjects in this study were students of class X IPS-1 SMA Negeri 2 Siabu which consisted of 21 female students and 9 male students. After applying the PAKEM model, it can be seen from the results of the mathematics learning interest questionnaire for students in the first cycle with an average of 56.58% while the average cycle II is 80.77%. Judging from the results of the first cycle of mathematics learning tests with 53.33% completeness percentage while the second cycle completeness percentage of 83.33%. The results of observations of the activities of students in the first cycle were 60.50%, while the average cycle II was 80.14%. From these results it can be concluded that the application of the PAKEM model can increase students' interest in learning mathematics at SMA Negeri 2 Siabu on the subject of trigonometric ratios on right triangles.